The effect of Royal jelly on liver enzymes and glycemic indices: A systematic review and meta-analysis of randomized clinical trials - Hossein Bahari; Shaghayegh Taheri; Mohammad Rashidmayvan; Sanaz Jamshidi; Mostafa Shahraki Jazinaki; Naseh Pahlavani (Elsevier, 2023)
Background: Royal jelly (RJ) may contribute to glycemic control and liver function through various mechanisms. The present study aimed to quantify the effect of RJ supplementation on these outcomes. Methods: A literature search of Web of Science, Scopus, and PubMed/Medline, was conducted for RCTs investigating the efficacy of RJ on plasma liver enzymes and glycemic indices. Weighted mean differences (WMDs) and 95% confidence intervals (CIs) were calculated for net changes using a random-effects model. Results: Ten RCTs were selected for inclusion in this meta-analysis. Combined estimate of effect sizes for the impact of RJ on neither the plasma liver enzymes nor the glycemic indices were statistically significant. Subgroup analysis showed a significant reduction of serum FPG in trials with intervention duration ≥ 8 weeks (WMD: −4.28 mg/dl, 95% CI −7.41 to −1.14 mg/dl, p = 0.007), and those conducted in non-healthy populations (WMD: −4.28 mg/dl, 95% CI −7.41 to −1.14, p = 0.007). Conclusion: RJ does not significantly affect liver function and glycemic profile of adult population. In trials with longer intervention and those conducted in non-healthy populations a significant reduction of serum FBG was observed. This meta-analysis should be repeated in the future, with more primary articles included, in order to provide conclusive results.